Tingkat Kepuasan DU/DI terhadap Kompetensi Siswa Tata Busana Pasca Program Teaching Factory di SMKN 3 Kedii - Rafiunnisa', Aliva Zhafira (Universitas Negeri Surabaya, 2020)
Abstract Teaching factory is a development of a dual system production and education unit that has been implemented in vocational school. Teaching factory program seeks to empower vocational schools to create graduates who are entrepreneurial and have competency expertise through the development of cooperation with industry. The purpose of this study was to describe the level of satisfaction of industry on the competence of students in 2nd grade of Clothing Study Program at SMKN 3 Kediri when carrying out Field Work Practices after implementing teaching factory learning. The research used is a descriptive research with ex post facto method. The research instrument was in the form of a questionnaire that had been validated by expert and was filled out by industry in collaboration with SMKN 3 Kediri totaling 11 industries. The data analysis method uses descriptive analysis. The results of the study stated that satisfaction with hard skill competence with an average of 80.51% and soft skill competence with an average of 77.51% and classified as satisfied. Keywords: industry satisfaction, student competence, teaching factory, fashion and apparel education